Florida Red Tide Perception: Residents versus Tourists - Nierenberg, Kate (2010)
The west coast of Florida has annual blooms of the toxin-producing dinoflagellate, Karenia brevis with Sarasota, FL considered the epicenter for these blooms. Numerous outreach materials, including Frequently Asked Question (FAQ) cards, exhibits for local museums and aquaria, public beach signs, and numerous websites have been developed to disseminate information to the public about this natural hazard. In addition, during intense onshore blooms, a great deal of media attention, primarily via newspaper (print and web) and television, is focused on red tide. However to date, the only measure of effectiveness of these outreach methods has been counts of the number of people exposed to the information, e.g., visits to a website or number of FAQ cards distributed. No formal assessment has been conducted to determine if these materials meet their goal of informing the public about Florida red tide. Also, although local residents have the opinion that they are very knowledgeable about Florida red tide, this has not been verified empirically. This study addressed these issues by creating and administering an evaluation tool for the assessment of public knowledge about Florida red tide. A focus group of Florida red tide outreach developers assisted in the creation of the evaluation tool. The location of the evaluation was the west coast of Florida, in Sarasota County. The objective was to assess the knowledge of the general public about Florida red tide. This assessment identified gaps in public knowledge regarding Florida red tides and also identified what information sources people want to use to obtain information on Florida red tide. The results from this study can be used to develop more effective outreach materials on Florida red tide.